The Effect of Accountability on Investment in Encouraging Regional Independence (A Study on Provinces in Indonesia) - Fidiatuljana Fidiatuljana; Sugianto Sugianto; Ernawaty Usman; Fajar Gilang Yudistira (International Journal of Economics, Management and Accounting (IJEMA), 2025)
Decentralization in Indonesia over the past 50 years has undergone many changes and updates, reflecting the need to increase the role of local governments. This study analyzes the extent of the influence of accountability on investment in increasing regional independence in Indonesia. The study used data from 34 provinces (170 observations) using purposive sampling techniques. The results of the study show that better audit opinions increase regional investment opportunities, but audit opinions issued by BPK have a negative impact on regional independence. Meanwhile, investment has a positive effect on regional independence but does not mediate the relationship between accountability and regional independence. The implications of this study are closely related to efforts to encourage regional independence through increased investment, so that local governments need to increase accountability in financial management, as reflected in the audit opinion, in order to create a conducive investment climate.